Conversational Analysis: Types and Function of Speech Acts in EFL Classroom Interactions - Darong, Hieronimus Canggung (JOLLT Journal of Languages and Language Teaching, 2024)
Understanding speech act production in EFL classroom interactions is crucial for enhancing teaching effectiveness and student engagement, as it sheds light on how language is used to convey meaning and manage social interactions in the learning environment. The purpose of this study was to analyze the speech act types and functions that were used by an EFL teacher and their students during classroom interactions. Observational data was collected and analyzed according to Conversation Analysis standards (CA). The findings of the study revealed that the types of speech acts produced by the teacher and students were influenced by their respective roles and statuses. Although the students produced fewer speech acts, they served the same functions as the teacher’s speech acts in terms of controlling and managing classroom interactions. As a result, the speech acts of both the students and teacher distributed authority in different ways during turn-taking and commodity exchanges. The practical knowledge and pedagogical use of the teacher-student relationship as a unique social event in the classroom context has the potential to effectively manage classroom interactions.